Gamma-ray Bursts: 15 Years of GRB Afterglows : Progenitors, Environments and Host Galaxies from the Nearby to the Early Universe - Castro-Tirado, Alberto Javier; Afonso, P. M. J.; Ahmad, S.; Ahn, K. B.; Ahn, K.-B; Allen, W.; Amati, L.; Amelushkin, A. M.; Aptekar, R. L.; Aptekar, R.; Asano, K.; Atteia, J.-L; et al. (EAS Publication Series, 2012)
Gamma-ray bursts (GRB) are amongst the most energetic phenomena in the Universe. In 1997 (more than 15 years ago), BeppoSAX allowed the detection of the first GRB X-ray afterglow, leading to the detection of afterglows at other wavelengths (optical, radio) in the following years, probing the cosmological distance scale. There are still many other open issues which still need to be addressed, regarding both theoretical and observational aspects: prompt emission and afterglow physics, progenitors (including Pop III stars), host galaxies, multi-messenger information, etc.
Keywords: Astronomy; Gamma ray bursts : Congresses; SCIENCE / Astronomy; gamma-ray bursts; Universe energies